2020
DOI: 10.1038/s41598-019-57140-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of glomerular DNA damage and DNA methylation with one-year eGFR decline in IgA nephropathy

Abstract: Accumulation of DnA double-strand breaks (DSBs) is linked to aging and age-related diseases. We recently reported the possible association of DnA DSBs with altered DnA methylation in murine models of kidney disease. However, DSBs and DnA methylation in human kidneys was not adequately investigated. this study was a cross-sectional observational study to evaluate the glomerular DnA DSB marker γH2AX and phosphorylated Ataxia Telangiectasia Mutated (pATM), and the DNA methylation marker 5-methyl cytosine (5mC) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Previous studies showed that epigenetic modifications play important roles in multiple autoimmune diseases, such as type 1 diabetes [4] and rheumatoid arthritis (RA) [5]. As for IgAN, there is a lot of evidence, suggesting that DNA methylation participates in the development of IgAN [6][7][8][9]. For example, DNA hypermethylation in promoter region of Cosmc and the molecular chaperone of core 1 β1,3-galactosyltransferase in peripheral blood mononuclear cells (PBMCs) of IgAN patients were shown to be because of low expression of the gene and increased level of aberrantly glycosylated IgA1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that epigenetic modifications play important roles in multiple autoimmune diseases, such as type 1 diabetes [4] and rheumatoid arthritis (RA) [5]. As for IgAN, there is a lot of evidence, suggesting that DNA methylation participates in the development of IgAN [6][7][8][9]. For example, DNA hypermethylation in promoter region of Cosmc and the molecular chaperone of core 1 β1,3-galactosyltransferase in peripheral blood mononuclear cells (PBMCs) of IgAN patients were shown to be because of low expression of the gene and increased level of aberrantly glycosylated IgA1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The same holds true for factors involved in other forms of DNA maintenance such as the KEOPS complex (Braun et al, 2017; Hecker et al, 2009) or KAT5, a contributor to DNA methylation and non-homologous endjoining repair (Hishikawa et al, 2019). The Itoh group further linked the proteinuric phenotype to DNA double strand breaks and methylation in the promotor region of slit diaphragm protein nephrin and established an association of DNA double strand breaks in glomeruli of patients suffering from IgA nephropathy (Hayashi et al, 2020; Hishikawa et al, 2020). Our analysis adds considerably to this body of evidence, as we identify multiple factors of DNA maintenance, in particular of NER, to be transcriptionally altered in glomeruli of various renal diseases involving pronounced podocyte damage and loss.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, glomerular DNA damage was found to be associated with declining kidney function 12 and cells isolated from the urine of patients suffering from diabetes and hypertension showed increased levels of DNA strand breaks 13 . However, a link between DNA damage and podocyte loss, to date, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that renal DNA DSBs may influence renal function of human. 42 However, DSBs in human kidneys have not been adequately investigated so far, and the status of DSBs in the glomeruli of patients with HN has not been reported yet. Our data showed that γH2AX-positive areas in the glomeruli were increased in patients with HN compared to the controls, which indicated that DNA DSB formation might contribute to the pathogenesis of HN.…”
Section: Food and Function Papermentioning
confidence: 99%